2013
DOI: 10.1111/jdv.12273
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the interleukin‐6‐174 gene and mannose‐binding lectin codon 54 gene polymorphisms and condyloma acuminatum

Abstract: These results suggest that the IL-6 G/G and MBL AA gene polymorphisms are potential risk factors and that the IL-6 G/C and MBL AB polymorphisms are a protective factor for occurrence and recurrence of CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The results of the present study showed that TC genotype of the +510 SNP is protective of sores in the genitals. Similarly, Aydogan et al (2014) had found that IL-6 gene at -174 SNP has an impact on genital warts. Most oral lesions among HIV positive patients are caused by opportunistic pathogens such as Candida spp or HSV, which manifest because of weakened immunity.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study showed that TC genotype of the +510 SNP is protective of sores in the genitals. Similarly, Aydogan et al (2014) had found that IL-6 gene at -174 SNP has an impact on genital warts. Most oral lesions among HIV positive patients are caused by opportunistic pathogens such as Candida spp or HSV, which manifest because of weakened immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that the T helper (Th) type 1/2 cell imbalance plays an important role in the incidence and recurrence of CA [5,6]. However, the mechanisms underlying this imbalance remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Previous studies have suggested that other factors including host immunogenetics are important in the pathogenesis of these HPV-related diseases. 4 , 5 Some studies have shown that the polymorphisms of human leukocyte antigen (HLA) genes are related with HPV infection. 6 , 7 HLA-G and HLA-DQB1 polymorphisms may represent risk factors in HPV infected subjects.…”
Section: Introductionmentioning
confidence: 99%